(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is devoted to the topic of innovative methods and means of organizing independent education of students. The article describes the forms and means of organizing independent education. Students’ independent works are discussed separately according to their characteristics. The importance of independent education in the educational process is justified from scientific and practical aspects.